(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Research was conducted on the possibility of open ing nepheline syenit es from the Sandyk deposit using the sin tering method with the application of so dium sulfate and sub sequent decomposition of the sinter with sulfuric acid. The infmuence of tempera ture (from 650 to 95 0°C) and sintering duration (from 30 to 120 minutes) on the extraction of alumin um and iron compounds was studied. It was found that the opt imal sintering condi tions for nepheline syenites with sodium sulfate are 750°C and a sintering durat ion of more than 60 minutes. It was shown that sintering of nepheline syenites with sodium sulfate and subsequent sulfur ic acid decomposition results in the ext raction of Al2O3 (53 .4%), Fe2O3 (22.4%), and REE (rare earth elements) (79.7-86.9%).